2018
DOI: 10.7181/acfs.2018.02075
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric follicular lymphoma of the parotid gland

Abstract: Primary malignant lymphoma rarely presents as a mass in the salivary gland. It accounts for about 1% of salivary gland tumors. The lymphomas of the parotid gland are mainly non-Hodgkin’s lymphoma of B-cell follicular type. It usually occurs in male adults and is very rare in children. In contrast to the intractable disease course of adult parotid follicular lymphoma, when occurred in children or adolescent, its prognosis is very good when it is first treated with surgical excision. Thus, a solitary follicular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
(10 reference statements)
2
3
0
Order By: Relevance
“…PTFL in the parotid gland area of children is rare. Jangyoun et al reported one case of PTFL occurring in the left parotid gland region (9), which had similar clinical characteristics to Case 2 in our study. PTFL is a localized disease, often without systemic symptoms; most cases are diagnosed at stage I or II, which can be treated by simple surgical resection.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…PTFL in the parotid gland area of children is rare. Jangyoun et al reported one case of PTFL occurring in the left parotid gland region (9), which had similar clinical characteristics to Case 2 in our study. PTFL is a localized disease, often without systemic symptoms; most cases are diagnosed at stage I or II, which can be treated by simple surgical resection.…”
Section: Discussionsupporting
confidence: 84%
“…The tonsil often occurs outside the node. PTFL can also arise in the liver, spleen, mediastinum, parotid gland, and other parts ( 8 , 9 ). Our patients presented with enlargement of the right cervical lymph node, left parotid gland mass, and left ear mass.…”
Section: Discussionmentioning
confidence: 99%
“…PTFL in the parotid gland area of children is rare. Jangyoun et al reported one case of PTFL occurring in left parotid gland region, 8 which was basically the same as the clinical characteristics of the patients in Case Two in this group. PTFL is almost a localized disease, usually without systemic symptoms, most of them are stage I or II, which can be treated by simple surgical resection.…”
Section: Discussionsupporting
confidence: 73%
“…The tonsil is often involved outside the node, and PTFL can also arise in the liver, spleen, mediastinum, parotid gland and other parts. 7,8 The patients in this group presented with right cervical lymph node enlargement, left parotid gland mass and left ear mass. PTFL in the parotid gland area of children is rare.…”
Section: Discussionmentioning
confidence: 95%
“…Although NHL is the second most common neoplasm in the head and neck region, primary parotid NHL accounts for only 1% to 4% of all parotid tumors [ 4 ]. The three most common subtypes of primary parotid NHL are extranodal marginal zone B-cell lymphoma of the mucosa-associated lymphoid tissue, follicular lymphoma, and diffuse large B-cell lymphoma, all of which originate from B lymphocytes [ 5 ].…”
Section: Discussionmentioning
confidence: 99%